Fighting to close the School of the Americas: Unintended consequences of successful activism. Issue 2 (3rd April 2017) - Weeks, Gregory
ABSTRACT: This article examines the structural and institutional changes that have occurred since the controversial United States School of the Americas (SOA) closed and its successor, the Western Hemisphere Institute for Security Cooperation (WHINSEC), opened in 2001. Placing these changes within a constructivist framework, the article uses the school as a case study to argue that human rights norm diffusion has both increased the amount of human rights in the curriculum and put the school in a much stronger institutional position than it had been. Human rights activists had successfully prompted change, but did not achieve their goal of closing the school. This article contributes to the literature by demonstrating how ideas about human rights can have important and lasting effects, but not always in ways that are either predictable or desirable for the political activists who spark them.